High‐performance Te‐doped Co3O4 nanocatalysts for oxygen evolution reaction. (15th December 2021) - Li, Guoru; Yu, Xiaoting; Yin, Fengxiang; Lei, Zhiping; Zhao, Xinran; He, Xiaobo; Li, Zhichun
Summary: To reduce the overpotential of electrocatalytic oxygen evolution reaction (OER) for high‐efficiency water splitting, a series of 2 to 5 nm ultrafine spinel Co3 O4 nanoparticles (NPs) with varied amount of lattice‐doped Te (XTe‐Co3 O4, X represents the nominal molar ratio Te/Co of 0, 2, 4, 6, 8%) as catalysts were prepared through a simple hydrothermal synthesis method. The 6%Te‐Co3 O4 catalyst was optimized to obtain the overpotential as low as 313 mV at 10 mA cm −2, a small Tafel slope of 75 mV dec −1 in 1 M KOH for OER, outperforming this series and many reported Co3 O4 ‐based catalysts. Te doping introduced lattice distortion and resulted in smaller size of Te‐Co3 O4 NPs with enlarged surface area for more accessible active sites. Oxygen vacancies were created to modify the electronic structure, improve the active sites density, and decrease the kinetic energy barriers of XTe‐Co3 O4 . The electronic conductivity of 6%Te‐Co3 O4 was improved to accelerate the charge transfer efficiency. All these effects contributed to promoting the reaction kinetics and minimizing the OER overpotentials for high‐performance electrocatalysis. Abstract : Te doping reduced particle size and regulated electronic structure of Co3 O4 NPs. 6%Te‐Co3 O4 presented plenty oxygen vacancies and improved conductivity. 6%Te‐Co3 O4 exhibited superior activity and stability as OER catalyst.